SUSTAINABILITY OF PUBLIC DEBT AND INEQUALITY IN A GENERAL EQUILIBRIUM MODEL. (4th June 2021) - Maebayashi, Noritaka; Konishi, Kunihiko
Abstract : This study investigates the relationship between the sustainability of public debt and inequality in an endogenous growth model with heterogeneous agents. We show that the threshold for the sustainability of public debt is related to not only the relative size of public debt but also inequality. In addition, this study examines the effects of budget deficit and redistributive policies on the sustainability of public debt and inequality. We show that an increase in the deficit ratio or the redistributive tax makes public debt less sustainable. If the economy falls into the unsustainable region as a result of the policy change, both public debt and inequality continue to increase.